Early Detection Of Rickets In Children Under Two Years And Prevention Of Its Complications: Clinical And Preventive Perspectives (The Peerian Journal, 2026)
Rickets remains a preventable yet persistent pediatric metabolic disorder characterized by defective mineralization of the growing skeleton. The disease is particularly critical in children under two years of age due to rapid bone development and increased nutritional demands. Despite well-established preventive strategies, delayed diagnosis continues to result in irreversible skeletal deformities and long-term functional impairment. This review critically examines the pathophysiological mechanisms underlying early rickets development, evaluates current diagnostic approaches, and discusses preventive strategies aimed at minimizing disease burden. Evidence indicates that biochemical alterations precede clinical manifestations, highlighting the importance of early screening. Timely intervention through vitamin D supplementation, nutritional optimization, and maternal health management significantly reduces complications. The findings emphasize that effective control of rickets depends more on early detection and prevention than on treatment of advanced disease.